The evolution of international security studies - Buzan, Barry; Hansen, Lene (Cambridge University Press, 2009)
International Security Studies (ISS) has changed and diversified in many ways since 1945. This book provides the first intellectual history of the development of the subject in that period. This is an unparalleled survey of the literature and institutions of ISS which will be an invaluable guide for all students and scholars of ISS, whether traditionalist, 'new agenda' or critical.